DINAMIKA KEJIWAAN TOKOH DALAM NOVEL ASSALAMUALAIKUM CALON IMAM KARYA IMA MADANIAH - Muhammad Ilham (EDU-KATA, 2021)
This study aims to: Describe the behavior of characters and the Dynamics of Psychology of characters in the novel Assalamualaikum Prospective Imam by Ima Madaniah. This study uses a qualitative method. The qualitative method in this study is: words, phrases, clauses, and sentences for each paragraph. Researchers used Sigmund Frued's Psychological Analytical approach. The life of the soul has three objectives, namely conscious, conscious, and unconscious. The results of the study indicate that character behavior is generally good. The psychiatric dynamics of the character experience a rise and fall due to internal and external factors. The mentality of Mr. Alif was originally not good. He almost did not acknowledge the existence of God, angry and frustrated because of various factors. Mr. Alif's life journey from bad to good. Nafisya psychic dynamics is able to overcome all problems ranging from kindergarten to university.